(untitled) (Journal on studies and research of academic knowledge, 2024)
This study investigates the effects of the drastic modality change in instruction due to the COVID-19 pandemic in a Spanish-language university course in the United States. The change from in-person to virtual instruction took place during the last week of March 2020. A qualitative analysis of 25 informal essays from a university-level Spanish-language classroom was performed through emergent categories in order to extract the topics that were most salient to students at the onset of the pandemic. While the pandemic affected every aspect of students’ lives, the results of this study indicate that the most salient dimensions are affective/emotional, family-related, academic, work and money related, and those pertaining to the responsibilities of governments and mass/social media.